Burnout and resilience among moroccan healthcare professionals: a comprehensive multi-hospital study - Guider, Hicham; Jaouhar , Samira; Bouzid, Jawad; Fadil, Wijdane; Himmouche, Naoufal; Cigarroa , Igor; El Alaiki, Ayoub; Hilali, Abderraouf; Hami, Hinde; Hadrya, Fatine (Jurnal Ners, 2025)
Introduction: This study examines the relationship between burnout and resilience among physicians and caregivers, aiming to determine whether the type of setting and demographic characteristics, such as gender and hospital hierarchy, have any impact. Methods: This multicenter cross-sectional study recruited 296 healthcare professionals through convenience sampling by self-administered questionnaires evaluating the Maslach Burnout Inventory and Connor-Davidson Resilience Scale. Data were analyzed using statistical methods, including correlation analysis and Multiple Correspondence Analysis (MCA). Results: From 158 valid responses, the mean scores for each scale were: EE at 28.44±12.90, DP at 9.96±6.47, and PA at 29.01±10.48; resilience was 23.78±7.71. All three had positive correlations with resilience. There were no significant differences in resilience or burnout between men and women. However, EE and PA were significantly correlated with male resilience, while all three burnout dimensions were associated with female resilience. Local hospitals reported higher mean scores for resilience and PA, whereas provincial hospitals exhibited elevated EE and DP scores. In regional hospitals, resilience was only associated with PA, whereas in provincial hospitals, it was correlated with both EE and PA. Conclusions: We found a high prevalence of burnout and inadequate resilience among healthcare professionals, underscoring the importance of considering these factors in the development of health policies and the implementation of preventive and remedial strategies.